Effectiveness of Range of Motion (ROM) Therapy and Warm Water Compress with The Orem Self Care Theory Approach Towards Improvement Strength Muscles in Non-Hemorrhagic Stroke Patients - Adirson Barbosa de Oliveira; Abdul Muhith; Umdatus Soleha; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2026)
Non-hemorrhagic stroke occurs when blood flow to the brain is stopped due to atherosclerosis or a blood clot that has blocked a blood vessel to the brain. As a result of brain disorders, it causes hemiplegia and hemiparesis. Many types of interventions are available for physical problems of hemiparesis, one of which is ROM therapy and Warm Water Compress. The purpose of this study was to analyze the effectiveness of Range Of Motion (ROM) therapy and Warm Water Compress with the Orem Self Care theory approach to Increasing Muscle Strength in Non-Hemorrhagic Stroke Patients. The design in this study was a Quasy Experiment with Pretest t and Posttest . The sample size was 44 with a Simple Random Sampling technique with 22 intervention groups and 22 controls. The intervention group was given ROM Exercises and Warm Water Compresses. Analysis used the Wilcoxon and Mann-Whitney tests to identify differences between the intervention and control groups with a significance level of a <0.05. The results obtained from the Wilcoxon Signed Rank Test analysis of Muscle Strength in Non-Hemorrhagic Stroke Patients in the intervention group p value = 0.000 and control p value = 0.000. The results show that there is an effect of ROM exercises and warm water compresses on increasing muscle strength in non-hemorrhagic stroke patients. ROM exercises and warm water compresses can be used as non-pharmacological therapy in the rehabilitation process for non-hemorrhagic stroke patients.